Demand side load management of smart grids using Intelligent trading/metering/billing system - Wang, Peng (2011)
Conventional power systems have been experiencing transition from centralized supply side management to decentralized supply & demand side management due to power system restructuring and addition of distributed generations (DGs) and Smart Grids (SGs) or Smart Distribution Systems (SDSs) with renewable power sources in the past two decades. Therefore load management under the new operating environment becomes more difficult than that under the conventional environment. This paper presents an Intelligent Metering/Trading/Billing System (ITMBS) and its implementation in Demand Side Load Management (DSLM) of SGs and SDSs. The ITMBS provides real time price information to customers through communication networks. Customers can adjust their demands through setting the operating time of some of the home appliances with energy storage feature such as heaters based on the real time prices to shift their consumptions and save cost. Customers can also participate in Direct Load Control (DLC) program in control center of a micro grid to shift their air condition demands through changing on and off circle based on the real time prices and weather conditions to save energy and to shift system peak load.